Urinoir Model as A Liquid Organic Fertilizer Producer of Nitrogen, Phospate and Potassium - Sri Puji Ganefati; Adi Heru Sutomo; Iswanto Iswanto (International Journal of Public Health Science (IJPHS), 2014)
Environment plays role as transmission media for various kinds of environmental based diseases such as Acute Respiratory Infection (ARI), Pulmonary Tuberculosis, Diarrhoea, Poliomyelitis, Measles, Hepatitis, Thypus and Herpes. This kind of disease stills a health problem for Indonesia. The mortality survey conducted in ten provinces by Sub-Directorate of ARI of the MoH of Indonesia in 2005 found that Pneumoniae as a type of ARI diseases was the greatest cause of death among infants (22.3 %) and under-five children (23.6 %), and based on Surkesnas report in 2010, the number of Thypus cases in Indonesia increased by 20.73 %. Meanwhile, among those diseases, Thypus, Hepatitis and Herpes can be transmitted by human urine, as well. On the other hand, urine can be processed becoming organic fertilizer because it consists of essential substances for plants growth, i.e. 80 % Nitrogen and Phospate and Potassium in the rest 20 %. 75 – 90 % of the Nitrogen is in form of Urea and only the small percentage of Ammonium and Creatinine. Meanwhile, 90 – 100 % of Phosphate and Sulphur   are in dissolved inorganic form and can be directly absorbed by plants. The use of liquid organic fertilizer is able for improving soil fertility which is depraved due to the continuing use of chemical fertilizer. The aim of the research was to understand the influence of the use of urinoir model in various urine detention times, on the concentration of the yielded Nitrogen, Phospate and Potassium (K) by conducting an experiment which employed post-test design. The results showed that the various urinoir models (I, II dan III) had effect on the concentration of those three substances of the liquid fertilizer (p < 0,001), and Model I (i.e. 5 day detention time) is found as the most appropriate urinoir model in producing the N, P an K subtances in the fertilizer.